2015
DOI: 10.1186/s12957-015-0519-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-center study of familial papillary thyroid cancer in China: surgical considerations

Abstract: BackgroundWhether familial papillary thyroid cancer (FPTC) is more aggressive than sporadic counterpart remains elusive, and the optimal clinical approach for FPTC is yet to be established. In this study, we investigated familial occurrence of PTC in China and reviewed our experience of its surgical treatment.MethodsThe clinical records of 248 consecutive patients with an established diagnosis of PTC who were admitted to Nanfang Hospital for thyroidectomy between January 2011 and June 2013 were analyzed in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
1
23
2
Order By: Relevance
“…Some groups report a lower age at diagnosis in familial cases [1,13]. However, we did not report a significant difference in age between familial and sporadic cases, like many others [3,[8][9][10][11][12]. This may be related to missed screening following the diagnosis in the other family members.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Some groups report a lower age at diagnosis in familial cases [1,13]. However, we did not report a significant difference in age between familial and sporadic cases, like many others [3,[8][9][10][11][12]. This may be related to missed screening following the diagnosis in the other family members.…”
Section: Discussioncontrasting
confidence: 77%
“…Most authors agree that fPTC is more aggressive than sPTC. This aggressiveness is characterized by multicentricity, larger tumour size, ETE, vascular invasion, and lymph nodal involvement [4,[8][9][10][11][12][13][14][15][16][17]. Since there is also contradictory data, it remains controversy [1,[18][19][20][21].…”
mentioning
confidence: 99%
“…In the previously mentioned Chinese study [56], patients with FNMTC had a significantly higher rate of metastases than the sporadic cohort (64% versus 34%, p=0.005). Zhang et al [57], in a more recent Chinese study reported similar findings.…”
Section: Clinico-pathological Features Of Familial Non-medullary Thyrmentioning
confidence: 92%
“…Although not all groups have found this to be statistically significant due to the already high rate of multifocality in sporadic NMTC [52], the majority of series report rates of multicentricity of approximately 50% in patients with a family history versus 30–40% in sporadic cases [50, 5356, 59, 62, 63]. Indeed, those groups with a sufficient number of cases to analyze those with 3 or more affected family members report rates of up to 68% in true papillary FNMTC [53].…”
Section: Clinico-pathological Features Of Familial Non-medullary Thyrmentioning
confidence: 99%
See 1 more Smart Citation